TBK1: A key regulator and potential treatment target for interferon positive Sjögren's syndrome, systemic lupus erythematosus and systemic sclerosis. (July 2018) - Bodewes, Iris L.A.; Huijser, Erika; van Helden-Meeuwsen, Cornelia G.; Tas, Liselotte; Huizinga, Ruth; Dalm, Virgil A.S.H.; van Hagen, P. Martin; Groot, Noortje; Kamphuis, Sylvia; van Daele, Paul L.A.; Versnel, Marjan A.
Abstract: Objective: Upregulation of type I interferons (IFN-I) is a hallmark of systemic autoimmune diseases like primary Sjögren's syndrome (pSS), systemic lupus erythematosus (SLE) and systemic sclerosis (SSc). Expression of IFN-I is induced by three different receptor families: Toll-like receptors (TLRs), RIG-like receptors (RLRs) and DNA-sensing receptors (DSRs). TANK-binding kinase (TBK1) is an important signaling hub downstream of RLRs and DSRs. TBK1 activates IRF3 and IRF7, leading to IFN-I production and subsequent induction of interferon stimulated genes (ISGs). The objective of this study was to explore the potential of BX795, an inhibitor of TBK1, to downregulate IFN-I activation in pSS, SLE and SSc. Methods: TBK1, IRF3, IRF7 and STAT1 were determined by RT-PCR in PAXgene samples and phosphorylated-TBK1 (pTBK1) was analyzed by flowcytometry in plasmacytoid dendritic cells (pDCs) from IFN-I positive (IFNpos) patients. Peripheral blood mononuclear cells (PBMCs) of pSS, SLE and SSc patients and TLR7 stimulated PBMCs of healthy controls (HCs) were cultured with the TBK1 inhibitor BX795, followed by analysis of ISGs. Results: Increased gene expression of TBK1, IRF3, IRF7 and STAT1 in whole blood and pTBK1 in pDCs was observed in IFNpos pSS, SLE and SSc patients compared to HCs. Upon treatment with BX795, PBMCs from IFNpos pSS, SLE, SSc and TLR7-stimulated HCs downregulated the expression of the ISGs MxA, IFI44, IFI44L, IFIT1 and IFIT3. Conclusions: TBK1 inhibition reduced expression of ISGs in PBMCs from IFNpos patients with systemic autoimmune diseases indicating TBK1 as a potential treatment target. Highlights: Phosphorylated TBK1 is upregulated in plasmacytoid dendritic cells of patients with interferon-I positive pSS, SLE and SSc. TBK1, IRF3, IRF7 and STAT1 gene-expression is upregulated in interferon-I positive patients with systemic autoimmunity. A TBK1 inhibitor downregulates interferon-I activation in TLR7-stimulated PBMCs. In PBMCs of patients with systemic autoimmunity interferon-I activation is downregulated by TBK1 inhibitors. Targeting TBK1 in interferon-I positive systemic autoimmune diseases is a promising treatment strategy.